Urodynamic diagnostics in the functional evaluation of the urinary incontinence - Pisarska, Magdalena (Menopause Review/Przegląd Menopauzalny, 2003)
Urinary continence is a result of the normal bladder and urethral function as well as the support and function of the pelvic floor support. Involuntary escape of urine is common and may result from functional or anatomic changes in any or all of these elements. An incontinence evaluation begins with a complete history and physical examination, which will provide a list of possible etiologic factors, an impression as to the type of incontinence, and the impact of urinary incontinence on the woman’s life. An assessment of the dynamics of the lower urinary tract function – urodynamics – during the storage and emptying phases will be necessary to diagnose and delineate a treatment plan. Proper utilization of urodynamic testing depends on the good understanding of its indications, techniques, and limitation. Urodynamics is not one specific test, but a series of tests. Other tests that are a part of the urodynamic evaluation include uroflowmetry, cystometry, and the assessment of the urethral pressure profile. In some cases urodynamics may be required to establish the diagnosis e.g. if we suspect the detrusor instability. Women must be evaluated to determine the way of treatment. The whole discussion regarding treatment options needs to include information about continence and the ability to voluntarily urinate, and first of all the possibility of nonsurgical management.